Ciprofloxacin-Loaded Spray-Dried Lactose Particles: Formulation Optimization and Antibacterial Efficacy - Sai Liu; Simon Gaisford; Gareth R. Williams (Pharmaceutics)
Background/Objectives: Bacterial infections in the oral cavity and outer ear require effective and targeted drug delivery systems. This study details the production of drug-loaded lactose microparticles, with the aim of creating antibiotic formulations for ultimate use in combatting oral and outer ear bacterial infections. Methods: Lactose particles were prepared via spray drying and optimized with varying ciprofloxacin (cipro) loadings to maximize the drug content. The particles were characterized to evaluate their performance in terms of physicochemical properties, drug-loading efficiency, drug-release kinetics, and antibacterial activity. Results: The resulting particles exhibited spherical morphology, efficient cipro loading (in the range of 1.1−52.9% w/w) and rapid cipro release within 5 h (achieving 70−81% release). In addition, they demonstrated effective concentration-dependent antibacterial activity against gram-positive Staphylococcus aureus and gram-negative Pseudomonas aeruginosa, with bacterial growth effectively inhibited for more than 24 h when particle concentrations reached the minimum inhibitory concentration. Conclusions: These findings highlight the potential of spray-dried cipro loaded lactose particles as an efficient approach for localized antibacterial treatment, offering a promising solution for managing bacterial infections in the oral cavity and outer ear.